2012
DOI: 10.1371/journal.pone.0031741
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Hematopoietic Inductive Microenvironment after Transplantation of VCAM-1-Modified Human Umbilical Cord Blood Stromal Cells

Abstract: The hematopoietic inductive microenvironment (HIM) is where hematopoietic stem/progenitor cells grow and develop. Hematopoietic stromal cells were the key components of the HIM. In our previous study, we had successfully cultured and isolated human cord blood–derived stromal cells (HUCBSCs) and demonstrated that they could secret hemopoietic growth factors such as GM-CSF, TPO, and SCF. However, it is still controversial whether HUCBSCs can be used for reconstruction of HIM. In this study, we first established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Many studies have demonstrated that the administration of MSC can protect and reverse radiation damage to bone marrow 1517 or other tissues 36–42 . However, the mechanisms underlining these beneficial effects are largely unknown and controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that the administration of MSC can protect and reverse radiation damage to bone marrow 1517 or other tissues 36–42 . However, the mechanisms underlining these beneficial effects are largely unknown and controversial.…”
Section: Discussionmentioning
confidence: 99%
“… 31 32 3) UCBI offers a large amount of G-CSF, GM-CSF, and CFU-F to increase the recovery of SAA. 21 22 23 24 25 26 27 It was noteworthy that intervals from first diagnosis to IST at baseline was longer in the UCBI+IST group than the IST group. The detailed reasons were as follows.…”
Section: Discussionmentioning
confidence: 97%
“… 21 22 23 24 3) Colony forming unit-fibroblastic (CFU-F) in UCB, which plays a critical role in hematopoietic microenvironment, improves the recovery of hematopoiesis. 25 26 27 4) HSCs from UCB are characterized by weak antigenicity that decreases the risk of GVHD. 28 These findings confirm the utility of UCB in various hematologic diseases, and considering the pancytopenia syndrome as the key property of SAA, we hypothesized that UCB could realize a good efficacy in treating SAA patients.…”
Section: Discussionmentioning
confidence: 99%
“…The sections were then stained with DAPI and examined with fluorescence microscope. The Hemapun 948 cold vacuum embedding technique was used to prepare Bone marrow sections [ 2 ] : Bone marrow pathological tissues was fixed in pre-cooled 4°C Bouin fixative solution for 1 h, washed with 0.1 ml/L sodium dimethylarsinate buffer in a 4°C refrigerator for 30 min, and dehydrated at 4°C in a gradient of alcohol concentrations for 10 min in each concentration. Living tissue blocks were then placed on the bottom of a mold with 2 ml of solution A in a type 1354 vacuum dryer for 2–4 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Although the survival rate of leukemia has been greatly improved due to new drugs, relapse of leukemia from minimal residue disease (MRD) remains a clinical challenge. The remaining leukemia stem cells in bone marrow (BM) following radiotherapy and/or chemotherapy are the primary cause for minimal residual disease (MRD) [ 1 , 2 ]. Therefore, modifying the BM microenvironment upon which leukemic stem cells depend for existence is a potential novel therapeutic strategy with less toxicity in the treatment of leukemia.…”
Section: Introductionmentioning
confidence: 99%